PEMANFAATAN TEKNOLOGI GEOFISIKA DAN PENGUATAN LITERASI MASYARAKAT UNTUK PENGELOLAAN AIR TANAH BERKELANJUTAN DI DESA JATIMULYO, KABUPATEN LAMPUNG SELATAN - Andri Yadi Paembonan; Dwi Miftha Kurnia; Randy Kurniawan; Stevy Canny Louhenapessy; Rozi Afdi; Fitri Rusmaladewi; Muhammad Rifqi Dwi Septian; Friska Hasugian; Putri Agustryani; Azman Munthoha Maula (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2026)
The availability of clean water is a crucial issue in Jatimulyo Village, South Lampung Regency, particularly during the dry season. Residents face difficulties accessing water sources due to a limited understanding of the subsurface groundwater potential. In response to this problem, a team from the Sumatra Institute of Technology (ITERA) conducted a community service activity aimed at mapping this groundwater potential. This activity utilized the geoelectric resistivity method to identify subsurface structures and determine the locations and depths of potential aquifers for drilled wells. In its implementation, the team collaborated with the local village government and involved participants from the Geophysical Engineering and Petroleum and Gas Engineering Study Programs. In addition to technical surveys, the team also conducted a socialization of their findings and provided education on groundwater utilization. This event, attended by residents, local neighborhood (RT) heads, and village officials, highlighted the importance of proper aquifer identification, well maintenance techniques, and strategies for ensuring water resource sustainability. This initiative received positive appreciation from the village head and residents, who hope the results of the ITERA study can provide a concrete solution to address the challenges of clean water availability in their region.